ORIENTEERING AS A PEDAGOGICAL COMPONENT - Denise Corrêa da Luz; Wanderley Marchi Júnior; Amauri Aparecido Bássoli de Oliveira (Journal of Physical Education, 2023)
ABSTRACT Orienteering is a sport that stands out for its pedagogical and formative potential because it includes physical, cognitive and social aspects that contribute to the integral education of students. Its reproduction or recreation in the school context can be a concrete experience of transformation and stimulus to the student leadership actions. The present study aims at showing the possibilities of inserting Orienteering in school units over the years of Basic Education by presenting it as a model of educational sport. This is a descriptive study with propositional characteristics. The specificities of this sport are shown based on Pierre Bourdieu’s relational perspective, the analytical model of the 5E’s proposed by Wanderley Marchi Júnior, and on the document analysis of the National Common Curricular Base. The pedagogically rich content that could be included in Physical Education classes is emphasized.